Implementasi Ajaran Konfusius Dalam Barongsai: Telaah Grup Satya Dharma Kelenteng Hok Hien Bio Di Kudus Jawa Tengah - Rosyid, Moh; Kushidayati, Lina (Al-Adyan: Journal of Religious Studies, 2021)
The purpose of this paper is to find a correlation between the teachings of Confucius and the lion dance group Satya Dharma at the Hok Hien Bio Temple in Kudus. The importance of research to provide understanding to the public that lion dance is not only a game or sport but Confucian values characterize the actors. Research data obtained by interviews and observations were analyzed descriptively qualitatively. The results showed that the lion dance group practiced regularly twice a week for free, followed by young people of all religions and ethnicities. This group was invited by residents in Kudus to the cultural carnival and people's party. The behavior of players and coaches follows the teachings of Confucius in the Si Shu Bible. First, it contains 8 confessions of faith (ba chen gui), realizing taboos, namely that what is immoral should not be seen (Hwi Lee But Si), heard (Hwi Lee But Thing), spoken (Hwi Lee But Gan), done (Hwi Lee But Tong), uphold the four pillars, understand the word (Ti Bing), receive the word (Siu Bing), uphold the word (Liep Bing), perfect the word (SingBing). Both behave in a friendly, gentle, honest, capable, obedient, sincere, simple, steady, and mighty manner, do tripusaka, are wise (Ti), loving (Jien), and brave (Yong). Third, abandon the 3 behaviors of arrogant, lazy, and extravagant, friendly, honest, and knowledgeable, have good relations with others (Ren Dao) and God (Tian/Shang Di) (Tian Dao).Tujuan tulisan ini adalah untuk mencari korelasi antara ajaran Konfusius  dan kelompok barongsai Satya Dharma di Kelenteng Hok Hien Bio di Kudus. Pentingnya riset untuk memberi pemahaman pada publik bahwa barongsai tidak hanya permainan atau olahraga tetapi nilai konfusius mewarnai para pelakunya. Data riset diperoleh dengan interviu dan observasi yang dianalisis secara deskriptif kualitatif. Hasil riset memperlihatkan bahwa kelompok barongsai berlatih rutin seminggu dua kali secara gratis, diikuti oleh anak muda lintas agama dan etnis. Kelompok ini diundang warga di Kudus pada acara kirab budaya dan pesta rakyat. Perilaku pemain dan pelatih menaati ajaran Konfusius dalam Kitab Suci Si Shu. Pertama, memuat 8 pengakuan iman (ba chen gui), mewujudkan pantangan yakni yang tak susila jangan dilihat (Hwi Lee But Si), didengar (Hwi Lee But Thing), diucapkan (Hwi Lee But Gan), dilakukan (Hwi Lee But Tong), menjunjung empat pilar, mengerti firman (Ti Bing), menerima firman (Siu Bing), menegakan firman (Liep Bing), menyempurnakan firman (SingBing). Kedua berperilaku 9 dengan ramah, lemah-lembut, jujur, cakap, patuh, tulus hati, sederhana, mantap, dan perkasa, melakukan tripusaka, bijaksana (Ti), cinta kasih (Jien), dan berani (Yong). Ketiga, meninggalkan 3 perilaku sombong, pemalas, dan foya-foya, bersahabat dengan lurus, jujur, dan berpengetahuan luas, berhubungan baik dengan sesama (Ren Dao) dan Tuhan (Tian/Shang Di) (Tian Dao).